An area-based study on intrapartum antibiotic prophylaxis for preventing group B streptococcus early-onset disease: advances and limitations. (18th July 2017) - Berardi, Alberto; Rossi, Cecilia; Bacchi Reggiani, Maria Letizia; Bastelli, Annalisa; Capretti, Maria Grazia; Chiossi, Claudio; Fiorini, Valentina; Gambini, Lucia; Gavioli, Sara; Lanari, Marcello; Memo, Luigi; Papa, Irene; et al.
Abstract: Introduction : The prevalence of maternal group-B-streptococcus (GBS) colonization and risk factors (RFs) for neonatal early-onset disease (EOD) in Europe are poorly defined. Large-scale information concerning adherence to recommendations for preventing GBS-EOD are lacking. Materials and methods : This was a 3-month retrospective area-based study including all regional deliveries ≥35 weeks' gestation (in 2012). The sensitivity, specificity, positive and negative predictive values, odds ratio and receiver operating characteristic (ROC) curve for intrapartum antibiotic prophylaxis (IAP) among full-term and preterm deliveries and prolonged membrane rupture (PROM) were calculated. Results : Among 7133 women, 259 (3.6%) were preterm (35–36 weeks' gestation). Full-term women were 6874, and 876 (12.7%) had at least 1 RF. Most women (6495) had prenatal screening and 21.4% (1390) were GBS positive. IAP was given to 2369 (33.2%) women (preterm, n = 166; full term, n = 2203). Compared to full-term, preterm women were less likely to receive IAP when indicated (73.2% versus 90.3%, p < 0.01). Full-term women represented the largest area under the curve (AUC, 0.87). PROM showed the highest sensitivity (98.6%), but the lowest specificity (6.9%) and AUC (0.53). Conclusions : Large-scale prenatal screening and IAP are feasible. Women delivering preterm are less likely to receive IAP when indicated. Most unnecessary antibiotics are given in cases of PROM.